2015
DOI: 10.1002/lsm.22367
|View full text |Cite
|
Sign up to set email alerts
|

Backscattering intensity measurements in optical coherence tomography as a method to identify parathyroid glands

Abstract: Besides the individual assessment of OCT images by interpreting morphological criteria, backscattering intensity measurements can reliably distinguish between different tissue entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Recently, it was reported that parathyroid, and to a lower extent thyroid, emit a unique autofluorescence signal in the near infrared region [11][12][13][14]. A few studies [15][16][17][18][19] reported the optical coherence tomography (OCT) to be a fairly reliable method for parathyroid identification, showing that representative tissue structures were visible in the OCT images, in both ex vivo [15] and in vivo [16] investigations. OCT and optical coherence microscopy (OCM) have shown to be promising in providing histology-like images of thyroid, parathyroid, adipose and muscle tissue [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that parathyroid, and to a lower extent thyroid, emit a unique autofluorescence signal in the near infrared region [11][12][13][14]. A few studies [15][16][17][18][19] reported the optical coherence tomography (OCT) to be a fairly reliable method for parathyroid identification, showing that representative tissue structures were visible in the OCT images, in both ex vivo [15] and in vivo [16] investigations. OCT and optical coherence microscopy (OCM) have shown to be promising in providing histology-like images of thyroid, parathyroid, adipose and muscle tissue [17].…”
Section: Introductionmentioning
confidence: 99%
“…OCT and optical coherence microscopy (OCM) have shown to be promising in providing histology-like images of thyroid, parathyroid, adipose and muscle tissue [17]. Sommerey et al showed that, in addition to the visual assessment of 2D OCT images, the intensity profile can be used as a method to distinguish parathyroid glands from thyroid, adipose and muscle tissue [18]. Hou et al automatically classified ex vivo parathyroid from thyroid, lymph node and adipose tissue using texture feature analysis and artificial neural networks [19].…”
Section: Introductionmentioning
confidence: 99%
“…OCT images of lymph nodes and parathyroid, thyroid, and adipose tissue display typical characteristics for each entity, facilitating a reliable differentiation. Conti de Freitas et al and our research group were able to confirm these favorable results ex vivo [1214]. However, due to technical problems, handling the OCT probe covered with a sterile sheath it was impossible to obtain similar results in vivo [15].…”
Section: Introductionmentioning
confidence: 76%
“…OCT has been developed rapidly and used in ophthalmology, dermatology, cardiology, and many other clinical fields. Attempts have been made to use OCT to scan in vivo and ex vivo parathyroid, thyroid, lymph nodes, and adipose tissue in thyroid surgery [13][14][15][16][17][18]. Armstrong et al used OCT to identify thyroid, parathyroid, fat, and lymph nodes for the first time [13] (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and specificity in distinguishing parathyroid was 84 and 94% , and 69 and 66% by human for ex vivo and in vivo experiments , respectively. The same research group identified parathyroid by measuring the backscattering intensity of their OCT images, the overall rate of correct classifications was 96.15% .…”
Section: Introductionmentioning
confidence: 99%